Clinical Applications of S53P4 Bioactive Glass in Bone Healing and Osteomyelitic Treatment: A Literature Review. (4th October 2015) - van Gestel, N. A. P.; Geurts, J.; Hulsen, D. J. W.; van Rietbergen, B.; Hofmann, S.; Arts, J. J.
Abstract : Nowadays, S53P4 bioactive glass is indicated as a bone graft substitute in various clinical applications. This review provides an overview of the current published clinical results on indications such as craniofacial procedures, grafting of benign bone tumour defects, instrumental spondylodesis, and the treatment of osteomyelitis. Given the reported results that are based on examinations, such as clinical examinations by the surgeons, radiographs, CT, and MRI images, S53P4 bioactive glass may be beneficial in the various reported applications. Especially in craniofacial reconstructions like mastoid obliteration and orbital floor reconstructions, in grafting bone tumour defects, and in the treatment of osteomyelitis very promising results are obtained. Randomized clinical trials need to be performed in order to determine whether bioactive glass would be able to replace the current golden standard of autologous bone usage or with the use of antibiotic containing PMMA beads (in the case of osteomyelitis).